Fungicides have complex effects on the wheat phyllosphere mycobiome - Knorr, Kamilla (PLoS One, 2019)
Effects of fungicide treatments on non-target fungi in the phyllosphere are not well known. We studied community composition and dynamics of target (Puccinia striiformis) and non-target fungi in wheat that was heavily infected with yellow rust. Mycobiotas in bulk leaf samples and individual leaves were studied by metabarcoding targeting the internal transcribed spacer-1 (ITS1) region of the ribosomal DNA. The amount of yellow rust in individual samples was quantified by qPCR (quantitative PCR). In addition, septoria tritici blotch (Zymoseptoria tritici), powdery mildew (Blumeria graminis), tan spot (Pyrenophora tritici-repentis), and yellow rust (P. striiformis) were visually evaluated. We showed how fungal communities were affected by three different broad-spectrum fungicides that had been applied at different timings and doses to control Puccinia striiformis. We showed that fungal content was relatively constant even after fungicide treatments. Principal component analysis demonstrated that communities from fungicide-treated plots could be separated from the communities in non-treated plots. We observed effects of fungicide treatments on fungal communities using different dose, timing and products. Some fungi, including the target organism P. striiformis were effectively controlled by most of the fungicide applications whereas some yeasts and also P. tritici-repentis increased after treatments. We demonstrated the feasibility of using metabarcoding as a supplement to visual assessments of fungicide effects on target as well as non-target fungi.